An Epidemiological Survey of Fatal Head Injuries Autopsied at a Tertiary Care Center in Dhulikhel, Nepal - Khan, Abdul Sami; Karki, Anish; Karki, Raj Kumar; Singh, Pankaj Kumar (Med Phoenix, 2024)
Introduction: The head is the most vital organ of body. National Advisory Neurological Diseases and Stroke Council has defined head injury as a morbid state, resulting from gross or subtle structural changes in the scalp, skull, and/or the contents of the skull, produced by mechanical forces. Traumatic brain injury has become a major health problem globally leading to morbidity and mortality which involves young aged individuals. Increasing use of motor vehicles among youths is one of the reasons for increasing traumatic brain injuries. Traffic safety laws has found to decrease the incidence of road traffic accidents and head injuries. Accidents at workplaces, mechanical violence, armed conflicts, terrorism and explosions are other causes of fatal head injuries. The present study aims at profiling the frequency of fatal head injuries, identify causes, common type and the most vulnerable population. Materials and Methods: This is a retrospective study of 399 cases autopsied at Department of Forensic Medicine, Dhulikhel Hospital, Kathmandu University of Medical Sciences from October 2020 to April 2022 out of which 122 cases of fatal head injuries were studied. Results: There are 104 male and 18 female of fatal head injuries. Individuals of 21-40 years are the most vulnerable victims. The study identifies road traffic accidents (50.81%) as the major cause of fatal head injury which is followed by physical assault (22.95%), fall from height (22.13%) and drowning (4.09%). Scalp contusion was seen in 44.26%. Skull was intact in 49.18%. Fracture of skull base was present in 19.67%. Combination of epidural, subdural and subarachnoid hemorrhages were present in 43.44%. Cerebral contusion and laceration were combinedly present in 13.11%. Conclusion: Road traffic accidents are the major cause of head injuries leading to the premature death of male population predominantly. Other than road traffic accidents, physical assault, fall from height, fall of heavy objects on body and drowning are the other causes for head injury. Adults of productive age group 21-40 years are highly prone to mortality and morbidity due to road traffic accidents. Legal bodies should pay proper attention to the road safety level to minimize such incidents and prevent premature deaths. Appropriate safety precautions while driving or even travelling by any vehicle should be adopted by drivers and passengers on their own.